DO FOREIGN INVESTORS ENHANCE THE ROLE OF FEMALE DIRECTORS IN CORPORATE FINANCING DECISIONS? - Chici Askotamiya; Suanti; Rumintar J. H. Marpaung (PT. Radja Intercontinental Publishing, 2026)
This study investigates whether board gender diversity influences the debt to asset ratio and examines the moderating role of foreign ownership within consumer non-cyclicals firms listed on the Indonesia Stock Exchange from 2020 to 2024. Analyzing a balanced panel of 170 firm-year observations across 34 companies using a Random Effect Model, the empirical evidence rejects both proposed hypotheses. The results indicate that the presence of female directors does not significantly reduce corporate leverage. Similarly, foreign ownership fails to moderate this relationship. These outcomes are largely explained by the low average female board representation (11.91%) in the sample, which falls well below the critical mass threshold required to actively shape financial policies. In this context, female participation functions primarily as tokenism. Furthermore, the highly dispersed nature of foreign ownership tends to substitute rather than reinforce board monitoring. This research highlights that merely having token female representation is insufficient to alter capital structure in an emerging two-tier board system, as corporate leverage remains overwhelmingly driven by persistent firm-specific characteristics.